Plastic deformation of metals under pressure treatment - Дудников, Анатолий Андреевич; Беловод, Александра Ивановна; Келемеш, Антон Александрович; Погорецкий, Александр Михайлович; Перелит, Игорь Васильевич (Eastern-European Journal of Enterprise Technologies, 2012)
The assessment questions of the metal plasticity and alloys processing and influence of different factors are considered